KAK AWAM’S STORYTELLING STRATEGY IN DELIVERING MORAL VALUES FOR CHILDREN - Hayati, Miratul; Lestari, Masroro Diah Wahyu; Nurmawahda, Nila (Journal of Early Childhood Education (JECE), 2020)
Storytelling is an exciting learning method that teachers can practice in learning activities. This study investigates the Kak Awam strategies in conducting storytelling to develop moral values in preschool children. This research uses descriptive qualitative. Data were collected by interview, observation, document analysis and video recording. The collected data were analyzed using Miles Huberman analysis, consisting of several stages: data collection, data reduction, data presentation and verification or conclusion. This study explains the storytelling strategies conducted by Kak Awam in delivering moral values can be implemented in learning activities at school.